COW URINE DISTILLATE AS A BIOENHANCER FOR ANTIMICROBIAL & ANTIPROLIFERATIVE ACTIVITY AND REDISTILLED COW URINE DISTILLATE AS AN ANTICLASTOGEN AGENT - Mohanvel, Sucharitha Kannappan; Rajasekharan, Satish Kumar; Kandhari, Trishna; Gopal Doss, Balaji Prasanna Kumar; Thambidurai, Yuvarani (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: The objective of this study was to prove that cow urine distillate (CUD) is a bioenhancer for antimicrobial activity and antiproliferative activity, redistilled CUD (RCUD) as an anticlastogen agent. Methods: The antimicrobial activity of rifampicin with CUD at different concentrations was determined against pathogenic Escherichia coli by well puncture method. The Penicillin and ciprofloxacin in combination with CUD at different/increasing concentrations against pathogenic E. coli culture were also determined by disc diffusion method. Sulforaphane (ACA) as an anticancer agent was extracted from cruciferous vegetables and purified by high-performance liquid chromatography. The Breast cancer cell lines (MCF-7) were treated with anticancer agents along with CUD in increasing concentrations. The anticlastogenic activity of RCUD in human peripheral lymphocytes was tested with clastogens such as manganese dioxide and hexavalent chromium. Results: CUD showed to enhance the antimicrobial activity of rifampicin with 20 Î¼l concentration by well puncture method; penicillin with increasing concentration of up to 80 Î¼l and ciprofloxacin up to 80 Î¼l, respectively, by disc diffusion method. The rate of degeneration of breast cancer cell lines (MCF-7) was increased with increasing concentration of CUD. Clastogen (MnO2) of 10 Î¼l with 200 Î¼l of RCUD showed effective anticlastogenic activity in agarose gel electrophoresis as the activity of clastogen decreased with increasing concentration of RCUD. Conclusion: CUD acts as a bioenhancer to increase antimicrobial and antiproliferative activity. RCUD showed a high level of anticlastogenic activity toward clastogen. Thus, cow urine is found to have special properties that can be used in combination with different therapeutic agents to cure several diseases such as tuberculosis, leprosy, and cancer. Further in vivo and clinical studies are required to confirm its therapeutic efficacy